Microbiological signature of PFAS-laden surface water foams - Harding, Barry (2021)
Presented by: Barry Harding – Technical Leader at AECOM, Barry.Harding@aecom.com Co-authors: Mike Jury, James Buzzell, Matt VanderEide Abstract: Surface Water Foams (SWFs) are frothy, buoyant, air-containing, aqueous masses encountered on rivers, open waters, and shorelines. They can be both naturally occurring and contain synthetic chemicals such as PFAS. In 2020, Michigan EGLE and AECOM conducted a SWF study, collecting 17 SWF from three rivers and two lakes in Michigan’s lower peninsula. One objective of the study was to determine the microbiological composition of SWF in supporting an understanding of natural processes potentially affecting SWF genesis. SWF were preserved in the field using DNA/RNA Shield® and analyzed by Zymo Research of Irvine, CA using Next Generation Sequencing, 16S/18S Ribosomal RNA, including bacteria and fungi. Functional genes were also mapped for several bacteria species and strains. Bray-Curtis β-diversity plots show five distinct microbial groups at a species level, consistent with 5 distinct geographically isolated surface water environments. The predominant Phyla identified are Proteobacteria (50.5%) > Bacteroidetes (21.8%) > Firmicutes (11.5%), > Actinobacteria (8.6%), and Ascomycota (fungi) (7.4%). Lake SWF samples show a distinct fungal signature, including the prominent presence of Saccharomyces cerevisiae. Analysis of functional genes suggest that SWFs are enzymatically active. Our current understanding suggests that SWF are biologically complex and contain natural surfactants. Biography: Barry Harding is a geologist and biologist with over 30 years of applied technical consulting experience in the environmental industry. He has worked on over 600 sites of environmental contamination on every continent except Antarctica. In his spare time he is an avid birder and amateur herpetologist. Open Restriction set for Item 117591 on 2021-04-23T20:06:25Z with date null by elm2@illinois.edu. Submitted by Elizabeth Meschewski (elm2@illinois.edu) on 2021-04-23T20:07:49Z ...